Risk Measurement with a Safety Belt: Pareto Meets Chebyshev - Karl-Heinz Tödter (Kredit und Kapital, 2012)
Risk Measurement with a Safety Belt: Pareto Meets Chebyshev Risk measures based on the Gaussian distribution are prone to understate the probability of extreme events. To capture fat tails and extreme events, we combine the Pareto law with finite variance bounds of Chebyshev. This density encompasses the tail behaviour of a wide range of random variables with unknown distribution. It provides a well-defined conservative measure of risks. Applications to measurement of forecast uncertainty and to value at risk and expected shortfall illustrate the approach empirically. (JEL D81, C53, G10) – – Risikomessung mit Sicherheitsgurt: Pareto trifft Tschebyschow Auf der Normalverteilung beruhende Risikomaße neigen dazu, die Wahrscheinlichkeit von extremen Ereignissen zu unterschätzen. Um extreme Ereignisse und dicke Enden von Verteilungen zu berücksichtigen, kombinieren wir die Pareto-Verteilung mit der Tschebyschow-Schranke für Zufallsvariablen mit endlicher Varianz. Diese Dichtefunktion umschließt das Verhalten einer großen Klasse von Zufallsvariablen und erlaubt eine wohldefinierte konservative Messung von Risiken. Anwendungen auf die Messung von Prognoseunsicherheit sowie den "Wert im Risiko" und den erwarteten Verlust im Risikofall illustrieren den Ansatz empirisch.
Keywords: D81; C53; G10; 330